A CONTRASTIVE ANALYSIS OF INTERROGATIVE SENTENCES IN ENGLISH AND INDONESIAN LANGUAGE - Khoirul Huda (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
Human beings are social creatures. They need a language for communication. A human being who came from different country has different language for communication. Although the languages are different, those have some similarities. The similarities of languages make the students easy to learn the languages as second or foreign languages. However, the differences of languages cause students face some difficulties to learn other languages. This research has analyzed some differences of interrogative sentences in English and Indonesian language in order to contribute positively in language learning and teaching. This research uses a method to know the differences between two languages. The method is contrastive analysis. Contrastive Analysis is a method of language analysis that popular in linguistic study in middle of 20th century. This method is used to contrast between two languages that have differences. Through this method, linguists or language learners find the differences which make them find the difficulties of languages which make them find the conveniences in learning. Interrogative sentences that have been analyzed in this research are sentences have essential roles in communications and learning language process too. Through this sentence, questioners obtain some information from respondent and teachers also invite the students’ idea. Before analyze the differences between two languages, this research presents the data presentation that explains the kinds of interrogative sentences in English and Indonesian language clearly. Then, researcher contrast two languages to find out differences of them. The differences between two languages are found, such as in placing of question words, the use of “who”, the form of interrogative sentences, tag questions. Based on this analysis can be known that interrogative sentences in English and Indonesian language have brief differences. The research findings have been found based on the structure and the uses of sentences.